People's Attitudes Towards the Quality of Physician-Patient Interactions in Primary Health Care Units in Fars Province - Leila Bazrafkan; Sedigheh Ebrahimi (Shiraz University of Medical Sciences, 2016)
Background: Changes in expectations and requirements of the end users of medical education "community members" and evolution in health services necessitate some changes in the medical education curriculum. To achieve this reform in curricula, obtaining insight into the health care needs of community members and their comments about their physicians is highly required in community-oriented education. This survey was conducted to determine the attitudes of health care receivers toward the general physicians' professional behavior in Fars province, Iran. Methods: This is a descriptive study and the subjects were the receivers of health care services. We selected 97 individuals in each city of Fars province using randomized-cluster sampling. The sample size increased to 150 in each city and overall 2500 individuals participated in the study. For data collection, an anonymous questionnaire was developed which was tested for the validity of the contents using the experts' views and reliability was checked using test-retest. The data were analyzed using SPSS 14 statistical software. Results: The results of this study revealed the participants' attitudes toward education, treatment and consultative services by physicians in Fars province. Overall, the response rate was about 95%. The patients rated the physicians' professional behavior, as one of the key determinants of their experiences with healthcare services. Moreover, 73.2% of the participants were fully satisfied with the quality of care they received from their physicians and 24.9% were satisfied to some extent. Conclusion: According to the results of the study, the physician's educational and consultative roles in medical education curricula must be reviewed and emphasized